Augmented hyperemia and reduced tissue injury in response to ischemia in subjects with the 34C > T variant of the AMPD1 gene - Riksen, N P (Blackwell Publishing Ltd, 2007)
INTRODUCTION: In patients with cardiovascular disease the 34C > T variant of the adenosine monophosphate deaminase (AMPD1) gene is associated with improved survival. We hypothesized that this variant results in enhanced intracellular formation of adenosine during ischemia, thereby increasing hyperemia and reducing tissue injury in response to ischemia. As increased intracellular adenosine formation would decrease the transmembranous adenosine concentration gradient, we hypothesized that the potentiating effect of the adenosine transport blocker dipyridamole on reactive hyperemia would be reduced in the subjects with the CT genotype. METHODS: We studied the forearm vasodilator response to ischemia (venous occlusion plethysmography) in 10 healthy subjects with the CT genotype and in 10 CC controls, matched for all relevant parameters of adenosine transport and metabolism. Reactive hyperemia was measured with and without concomitant administration of the adenosine transport blocker dipyridamole into the brachial artery (7.4 nmol/min/dl of forearm tissue). In comparable groups, ischemia-reperfusion injury was assessed in the thenar muscle by (99m)Tc-annexin A5 scintigraphy after intermittent forearm exercise during 10 minutes of ischemia. At reperfusion (99m)Tc-annexin A5 was administered intravenously. Targeting of annexin was expressed as percentage difference between experimental and contralateral thenar muscle. RESULTS: Forearm blood flow (FBF) in response to 2 and 5 minutes of ischemia was higher in the CT genotype group than in controls, whereas maximum vasodilation (induced by 13 minutes of ischemia) did not differ (25.4 ± 2.5, 32.7 ± 2.2, and 38.6 ± 2.6 ml/min/dl in the CT group versus 21.9 ± 2.2, 28.5 ± 2.4, and 41.0 ± 3.3 ml/min/dl in controls, P=0.03). Dipyridamole potentiated reactive hyperemia in both groups, but this effect of dipyridamole was significantly less in the subjects with the CT genotype (P=0.04). At 1 and 4 hours post-injection, annexin targeting was 5.2 ± 1.8% and 3.5 ± 2.3% in the CT group versus 8.9 ± 3.4% and 9.8 ± 3.9% in the controls (n=7; P=0.03). CONCLUSIONS: The 34C > T variant in the AMPD1 gene augments vasodilation and reduces tissue injury in response to forearm skeletal muscle ischemia. Most probably, this is due to increased intracellular adenosine formation, which decreases cellular uptake of adenosine which is formed in the extracellular compartment. These mechanisms could contribute to the survival benefit of cardiovascular patients with this variant allele.